Eight ‘truths’ about suicide - Rachel Gibbons (BJPsych Bulletin)
This paper summarises themes that have emerged from 14 years of study of suicide and work with those bereaved. It is based on a talk given in many clinical settings over the past 10 years. I describe my own emotional journey following impactful deaths and summarise personal ‘truths’ about suicide that have emerged over time. Case studies used for illustration are composites taken from clinical practice; accounts of relatives and other survivors of suicide; and data taken from many sources including suicide audits in mental health organisations, the police and transport services, and from the examination of coroners’ records. The intention is to assist open dialogue about the nature of suicide, to contribute to the understanding of the impact on those bereaved and to encourage open-hearted clinical engagement with those who are suicidal.